Upconversion luminescence and optical thermometry properties of transparent oxyfluoride glass ceramics embedded with Ba4Y3F17: Yb3+, Er3+ nanocrystals. Issue 38 (9th September 2020) - Li, Yong; Wang, Wenming; Pan, Yan; Chen, Hongmei; Cao, Qianwen; Wei, Xiantao
Abstract : Transparent glass ceramic embedded with Ba4 Y3 F17 : Yb 3+, Er 3+ nanocrystals can be realised as a promising temperature sensor. Abstract : Transparent glass ceramics incorporated with Ba4 Y3 F17 : Yb 3+, Er 3+ nanoparticles are successfully elaborated through melt-quenching method. The crystal structure and morphology of Ba4 Y3 F17 nanocrystals were confirmed by X-ray diffraction, selected-area electron diffraction, and transmission electron microscopy. Compared to their glass counterpart, the pronounced enhancement of upconversion emission confirmed the incorporation of Yb 3+ and Er 3+ into precipitated Ba4 Y3 F17 nanocrystals. In addition, longer luminescence lifetimes as well as an increased rise time in the decay curve were observed. Furthermore, the dependence of upconversion luminescence behaviors on temperature was systemically investigated through the fluorescence intensity ratio technique under an excitation of 980 nm. The FIR of the two thermally coupled energy levels of Er 3+ ion was validated to be suitable for their use as temperature probes. The maximum thermal sensitivity was approximately 1.13% K −1 at 300 K. Besides, the laser-induced thermal effect was demonstrated to be imperceptible in the glass ceramic sample. The results imply that the Yb 3+ –Er 3+ -codoped Ba4 Y3 F17 glass ceramics can be used as potential candidates for temperature sensing.